Influência da densidade de pombeiro (Combretum laxum) sobre a comunidade de anfíbios anuros em uma localidade do Pantanal Norte, Poconé, Mato Grosso, Brasil - Rodrigues, Tainá Figueras Dorado (2012)
The expansion of woody species like the shrub Combretum laxum (“pombeiro”) in areas of open field vegetation (CLN) in the Pantanal affects the original landscape and reduces habitat diversity for many animal species. In wetlands, anuran amphibians respond quickly to variations in the density of vegetation and thus can be employed as bioindicators of environmental impacts caused by habitat shifts. The goal of this work was to investigate the influence of selected environmental variables (soil moisture, distance to areas indicative of residual moisture, and particularly, coverage by C. laxum) on the richness, abundance and composition of anuran assemblages in a locality in two farms in the northern Pantanal, municipality of Poconé, Mato Grosso. Samplings of anurans were made in 17 plots in CLN with varying degrees of coverage by "pombeiro", by using pitfalls with drift fences and active searches (both visual and acoustic). The non-metric method of multidimensional scaling (NMDS; Bray-Curtis) was used to reduce the community's data. Multiple regressions and multivariate regressions were used to analyze the relationship of environmental variables with local richness, abundance, and composition of anurans. A total of 1.203 anurans were recorded, in 21 species and five families. Both richness and abundance of anurans were negatively related to the coverage by C. laxum. Moreover, changes in composition of the community were linked only to the degree of coverage by C. laxum. Richness diminished, also, with distance to areas indicative of residual moisture, which might reflect the need of amphibians to seek more suitable habitats to spend the drought. Scinax acuminatus was the only species recorded exclusively in CLN. Scinax nasicus, S. fuscovarius, Rhinella major, R. schneideri and Dendrophsophus minutus were found both in CLNs and in areas with little expansion by C. laxum. Three species, Leptodactylus cf. latrans, Trachycephalus typhonius and Pseudis paradoxa, were recorded only in plots densely covered by “pombeiro”. With aquatic habitats, individuals of P. paradoxa were locally abundant and possibly use “pombeirais” for shelter, foraging, or even as migratory routs. Changes in vegetal communities, such as those caused by the mono-dominance of "pombeiro", may result in habitat loss for anurans of open areas in the Pantanal. CLNs and areas with low level of coverage might have more varied microhabitats and greater environmental heterogeneity than "pombeirais". Thus, at the same time that there is a need of establishing strategies for the management of plant species with the potential of great expansion over natural open habitats in the Pantanal, there is also a need of better understanding the role of such “new” habitats in maintaining local biodiversity.